Galen's treatise Peri alypias (De indolentia) in context : a tale of resilience - Petit, Caroline, 1976- (Studies in Ancient Medicine, 2018)
This collective volume arises from a Wellcome-funded conference held at the University of Warwick in 2014 about the "new" Galen discovered in 2005 in a Greek manuscript, De indolentia . In the wake of the latest English translation published by Vivian Nutton in 2013, this book offers a multi-disciplinary approach to the new text, discussing in turn issues around Galen's literary production, his medical and philosophical contribution to the theme of avoiding distress (ἀλυπία), controversial topics in Roman history such as the Antonine plague and the reign of Commodus, and finally the reception of the text in the Islamic world. Gathering eleven contributions by recognised specialists of Galen, Greek literature and Roman history, it revisits the new text extensively.